THE ROLE OF SCHOOL LITERACY MOVEMENT (SLM) IN INCREASING STUDENT INTEREST IN READING: A LITERATURE REVIEW - Prihartini, Arina Amalia; Binti Ali, Nooraihan; Fitri, Hilwa Alfiani (Universitas Islam Negeri Mataram, 2023)
This study was prompted by students' lack of interest in reading and literacy abilities in Indonesia. In 2015, Indonesia ranked 62 out of 76 countries in the PISA survey. The government created the School Literacy Movement (SLM) program in 2016, in response to students' low literacy scores and reading interest. The government expects that this program will increase reading enthusiasm in Indonesia. The objective of this study was to investigate the impact of the SLM on students' reading interest. The method utilized is a literature research or review. A literature study is a research design used to collect data sources on a certain topic. As the stage of searching for literary sources, data collecting for the study of literature is carried out using a database search tool. This research is conducted by synthesizing conceptual or empirical articles pertinent to the study to be conducted. It begins with the analysis of articles pertinent to the topic to be reviewed, this entails discussing and reviewing the articles by identifying and classifying them based on the elements to be reviewed from multiple articles that discuss essentially the same subject. According to the papers discovered and evaluated, the school literacy movement has a positive role on students' reading interest, this is proven by the increase of library visits, the increase in problem-solving skills in the learning process, the increase in students' capacity to write Wall Print Magazines, and the increase in the number of students who read before class. As a result, it can be inferred that SLM has a role in enhancing children's interest in reading through various school-based programs and activities.